A New Method for Identifying the Life Parameters via Radar. (30th January 2007) - Jianqi Jianqi, Wang Wang; Chongxun Chongxun, Zheng Zheng; Guohua Guohua, Lu Lu; Xijing Xijing, Jing Jing
Abstract : It has been proved that the vital signs can be detected via radar. To better identify the life parameters such as respiration and heartbeat, a novel method combined with several signal processing techniques is presented. Firstly, to improve the signal-to-noise ratio (SNR) of the life signals, the signal accumulation technique by FFT is used. Then, to restrain the interferences produced by moving objects, a dual filtering algorithm (DFA) which is able to remove the interferences by tracing the interfering spectral peaks is proposed. Finally, the wavelet transform is applied to separate the heartbeat from the respiration signal. The method cannot only help to automatically detect the existence of human beings effectively, but also identifying the parameters like respiration, heartbeat, and body-moving signals significantly. Experimental results demonstrated that the method is very promising in identifying the life parameters via radar.